Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1211/jpp.59.4.0015
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antinociceptive properties of blueberry extract(Vaccinium corymbosum)

Abstract: Blueberries are among the edible fruits that are recognized best for their potential health benefits. The crude extract from Vaccinium corymbosum was assessed in anti-inflammatory and antinociceptive models. The crude hydroalcoholic extract was administered orally at doses of 100, 200 or 300 mg kg (-1) for all the assays. In the carrageenan test, the crude extract reduced rat paw oedema by 9.8, 28.5 and 65.9%, respectively. For the histamine assay, the reductions of oedema were 70.1, 71.7 and 81.9%, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 29 publications
0
19
2
1
Order By: Relevance
“…These results could be attributed to the structural features of the polyphenols and/or other compounds present in each fruit extract. Compared to previously published works, TP reported in the present study was lower than those reported in maqui (4570 mg GAE/ 100g DW 19 ), calafate (3490 mg GAE/100 g DW 20 ), and blueberry extracts (5660 mg catechin equivalents/100 g fresh weight [FW] 21 ). This could be explained by the use of a nonacidified hydroalcoholic extract, which probably resulted in a decrease extraction efficiency of anthocyanins FIG.…”
Section: It Has Been Recognized That Increased Body Adiposity Is Habicontrasting
confidence: 96%
“…These results could be attributed to the structural features of the polyphenols and/or other compounds present in each fruit extract. Compared to previously published works, TP reported in the present study was lower than those reported in maqui (4570 mg GAE/ 100g DW 19 ), calafate (3490 mg GAE/100 g DW 20 ), and blueberry extracts (5660 mg catechin equivalents/100 g fresh weight [FW] 21 ). This could be explained by the use of a nonacidified hydroalcoholic extract, which probably resulted in a decrease extraction efficiency of anthocyanins FIG.…”
Section: It Has Been Recognized That Increased Body Adiposity Is Habicontrasting
confidence: 96%
“…Vaccinium corymbosum, isolated from blueberries, shows anti-inflammatory and antinociceptive activities. Thus, its consumption will be beneficial for the therapy of inflammatory diseases (Torri et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…40 Evaluation of the pharmacological properties of the compounds isolated from the active fractions pointed out that anthocyanins possess strong antioxidant=anti-inflammatory activities, as well as the ability to inhibit lipid peroxidation and the inflammatory mediators cyclooxygenase-1 and -2, including cell migration. Cyanidins are reported to possess anti-inflammatory properties comparable to those of commercial products naproxen and ibuprofen.…”
Section: Discussionmentioning
confidence: 99%